2020
DOI: 10.1038/s41598-020-69609-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an InGaN superlattice pre-layer on the performance of semi-polar (11–22) green LEDs grown on silicon

Abstract: It is well-known that it is crucial to insert either a single InGaN underlayer or an InGaN superlattice (SLS) structure (both with low InN content) as a pre-layer prior to the growth of InGaN/GaN multiple quantum wells (MQWs) served as an active region for a light-emitting diode (LED). So far, this growth scheme has achieved a great success in the growth of III-nitride LEDs on c-plane substrates, but has not yet been applied in the growth of any other orientated III-nitride LEDs. In this paper, we have applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(159 reference statements)
0
2
0
2
Order By: Relevance
“…[ 62 ] Zhao et al inserted SL to semipolar green LEDs and found an improvement in IQE due to the reduced point defect density. [ 63 ] The IQE improvement for semipolar LED with SL was not significant as its c ‐pane counterparts because extra misfit dislocations were introduced as nonradiative recombination centers. The influence of thickness ratio of InGaN to GaN in prestrained structure was investigated by Qi et al Degraded crystal quality was observed in green LED with low thickness ratio, whereas LED with high thickness ratio showed high series resistance, indicating the importance of suitable design of prestrained structure.…”
Section: Prestrained Structurementioning
confidence: 99%
“…[ 62 ] Zhao et al inserted SL to semipolar green LEDs and found an improvement in IQE due to the reduced point defect density. [ 63 ] The IQE improvement for semipolar LED with SL was not significant as its c ‐pane counterparts because extra misfit dislocations were introduced as nonradiative recombination centers. The influence of thickness ratio of InGaN to GaN in prestrained structure was investigated by Qi et al Degraded crystal quality was observed in green LED with low thickness ratio, whereas LED with high thickness ratio showed high series resistance, indicating the importance of suitable design of prestrained structure.…”
Section: Prestrained Structurementioning
confidence: 99%
“…Авторы [170][171][172] продемонстрировали, что светоизлучающие диоды GaN с длиной волны излучения около 530 nm могут быть синтезированы на полуполярном GaN (11−22), выращенном на структурированных подложках Si (113).…”
Section: приборы на основе полуполярного Gan на структурированных под...unclassified
“…To enhance the optoelectronic performance of LD, researchers have made a lot of efforts in the direction of alleviating the strain accumulation in the active region and improving crystal quality. The commonly used methods include: growing a stress compensation layer in the active region before MQWs; 5,6 using ternary or quaternary compounds with the similarity to the lattice constants of InGaN as quantum barrier layer materials; 7,8 growing MQWs in the nonpolar or semipolar surfaces; 9 and doping GaN quantum barrier layer with silicon, etc. 10 These methods typically use a low indium content waveguide layer for good optical confinement.…”
mentioning
confidence: 99%